Real-World Experience of Imipenem–Relebactam Treatment as Salvage Therapy in Difficult-to-Treat Pseudomonas aeruginosa Infections (IMRECOR Study) - Isabel Machuca; Arantxa Dominguez; Rosario Amaya; Cristina Arjona; Irene Gracia-Ahufinger; Maravillas Carralon; Rosa Giron; Isabel Gea; Natividad De Benito; Andres Martin; Fatima Galan; Jose Antonio Martinez; et al. (Infectious Diseases and Therapy)
Abstract Introduction Difficult-to-treat-resistant (DTR) infections caused by Pseudomonas aeruginosa represent a global public health threat, prioritizing the search and development of new antibiotics for this microorganism. Methods We present the real-life experience of the compassionate use of imipenem/cilastatin/relebactam in a descriptive study involving 14 patients with DTR-P. aeruginosa infection and limited treatment options. Results The primary source of infection was skin and soft tissue infection, 57.1% (8/14), followed by respiratory infection-pneumonia, 28.6% (4/14). At the onset of infection, 71.4% (10/14) of patients were in the intensive care unit (ICU). All our patients had a Charlson Score of ≥ 3. Septic shock was observed in 64.3% (9/14) of patients. The median treatment duration was 15 days, and no patient experienced an adverse event that required treatment interruption. All-cause 30-day mortality was observed in 42.9% of cases (6/14), while clinical efficacy and microbiological success were observed in 64.3% (9/14). Conclusions Imipenem/cilastatin/relebactam may represent a treatment option for patients with DTR-P. aeruginosa infections, which should be validated in prospective clinical trials.